You just got cheated!: understanding white-collar crime - Mathew, Sibichen K. (SAGE, 2020)
You Have Been Cheated -- What Constitutes White-Collar Criminality? -- Where is Your Money? The Investment Frauds and the Victims -- Too Large to Fail; Too Big to Jail? Corporate Frauds and Victims -- Profits through Peril: Corporate Victimization of The Planet -- Blood Suckers: Occupational Abuses -- The Unholy Nexus: The Powerful World of Bribery and Corruption -- Your Life in Their Hands: Crimes in Health and Pharma Sectors -- Gullible Victims: Corporate Abuse of Consumers -- White-Collar Crimes in Education -- In the Name of God: The Victims of Religious Crimes -- Cyber Victims -- Why People Commit White-Collar Crimes and Why Others Fall Victim? -- Curbing White-Collar Crime and Preventing Victimization -- Heroes Turn Victims: Whistleblowers of White-Collar Crimes.